-3v+48=6(v+5)

Simple and best practice solution for -3v+48=6(v+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3v+48=6(v+5) equation:



-3v+48=6(v+5)
We move all terms to the left:
-3v+48-(6(v+5))=0
We calculate terms in parentheses: -(6(v+5)), so:
6(v+5)
We multiply parentheses
6v+30
Back to the equation:
-(6v+30)
We get rid of parentheses
-3v-6v-30+48=0
We add all the numbers together, and all the variables
-9v+18=0
We move all terms containing v to the left, all other terms to the right
-9v=-18
v=-18/-9
v=+2

See similar equations:

| -8-k=-2-6k+6k | | 1024=4x+2 | | n+285=960 | | s+113=995 | | 2(5x+8)=41+27 | | r+4=-r+10 | | -8y+6(y-2)=-24 | | 10r=-8(-r+1) | | 22=u/19 | | -33=9(3b+4) | | (3x+12)+(2x+42)=180 | | 4x2+10x=x2-x+4 | | n/45=30/125 | | -6a-8(2-16a)=4(19a+19) | | -6g-5g+14=14-11g | | u-70=39 | | 5x-1=-2x-8 | | 2(2x+4)=10x | | p-899=-557 | | 11+5z-20=1+5z | | -2+n/4=0 | | y/5/3+5=25/6 | | p-588=218 | | -6a-8(2-16a)=4(19a+149) | | 18m-12m+16=8m-8 | | 3p-p=14 | | 18d-4+3/8d-4=5 | | 14j=-196 | | -14w+12w-4=14-w | | -40+k=2k | | 3x+15=55-2x | | 45x+60=55x |

Equations solver categories